The effect of ownership structure and non performing loan on financial performance of banking companies in ASEAN - Luana, Mona; Adam, Mohamad; Widiyanti, Marlina; Fuadah, Lukluk (International journal of economic perspectives, 2024)
This study analyzes the effect of ownership structure and the level of Non-Performing Loan (NPL) on the financial performance of banking companies in ASEAN, as measured by Return on Equity (ROE). The study uses secondary data from the annual reports of 40 banking companies in ASEAN for the period 2019-2023, using multiple regression analysis methods. The results showed that managerial ownership has a positive but insignificant effect on ROE. In contrast, institutional ownership shows a negative and significant influence on ROE, indicating that strict supervision by institutions can limit management flexibility in strategic decision making. NPL is shown to have a significant negative effect on ROE, indicating that high non-performing loans can reduce the profitability and financial stability of banking companies. The findings are expected to assist bank managers and policy makers in designing optimal strategies to improve financial performance and manage credit risk.